The orb-weaving spider Eustala described from southern Brazil : (Araneae, Araneidae) - Poeta, Maria Rita Muniz (2013)
The Araneidae Clerck, 1757 has 3029 species in 168 genera. They are common in nature, weaving orbicular bidimensional webs on trees and bushes and, apparently, have nocturnal habits. Spiders of Eustala Simon, 1895 occur throughout all American continent and it seems to be the most speciose Neotropical Araneidae genus. The genus contains about 90 species, 16 of which have been described from Brazil. The male is characterized by the palpus with only one patellar macroseta; conic, whitish hanging down posteriorly median apophysis and the terminal apophysis is a sclerotinized extension, resting on a transparent, baloon-like, subterminal apophysis. The females are characterized by the epigynum with ringed scape pointed anteriorly. The most common pattern color on the abdomen dorsum is a folium. However, this could vary from specimen to specimen, being more or less pigmented. Although frequently collected, species of this genus are poorly known, at present, there are just a few studies on the genus from South America. Thus this study aims to contribute to the knowledge of the Brazilian species of Eustala, through diagnosis and illustrations of species from Southern Brazil, giving continuity to the work initiated about the genus on Rio Grande do Sul state. In order to carry out this study, Eustala material from several arachnological collections was analyzed. Illustrations were made with the aid of camera lucida coupled to the stereoscopic microscope. The left male palpus was illustrated on mesal and ventral views; the epigynum was illustrated on ventral, posterior and lateral views. In current study Eustala ulecebrosa (Keyserling, 1892), from Rio Grande do Sul and E. mourei Mello-Leitão, 1947, from Paraná are illustrated and redescribed. Eight new species from Southern Brazil are described: E. guarani sp. nov., from Paraná; E. catarina sp. nov., from Santa Catarina and E. ericae sp. nov., E. cidae sp. nov., E. lisei sp. nov., E. cuia sp. nov. and E. farroupilha sp. nov, all based on males and females and E. eldorado sp. nov., based only on males, from Rio Grande do Sul. Eustala albiventer (Keyserling, 1884), E. taquara (Keyserling, 1892), E. minuscula (Keyserling, 1892), E. itapocuensis Strand, 1916, E. photographica Mello-Leitão, 1944, E. levii and E. palmares, Poeta, Marques & Buckup, 2010 present new distribution records from Brazil and E. perfida Mello-Leitão, 1947 has a first record in Uruguay.